Respostas
respondido por:
5
Usando a fórmula y-yo=m(x-x0)
y-2=-4(x+3)
-4x-12-y+2=0
4x+y+10=0 (em forma geral)
y=-4x-10 (em forma reduzida)
y-2=-4(x+3)
-4x-12-y+2=0
4x+y+10=0 (em forma geral)
y=-4x-10 (em forma reduzida)
respondido por:
6
(x₀, y₀) = (-3 , 2)
m = - 4
Como: y - y₀ = m (x - x₀)
Temos:
y - 2 = - 4[x - (- 3)]
y - 2 = -4 [x + 3]
y - 2 = - 4x - 12
y = - 4x - 12 + 2
y = - 4x - 10
m = - 4
Como: y - y₀ = m (x - x₀)
Temos:
y - 2 = - 4[x - (- 3)]
y - 2 = -4 [x + 3]
y - 2 = - 4x - 12
y = - 4x - 12 + 2
y = - 4x - 10
Anônimo:
Cometi um equívoco onde há -2, devia ser - 3. Mal ai.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás